Technology Readiness and Acceptance Model: Analisis Kesiapan Pengguna dalam Penerapan Rekam Medis Elektronik di RSUD Provinsi NTB - Nurul Khatimah Ismatullah; Reni Chairunnisah; Helmina Andriani (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2025)
Implementation of RME is a complex process, involving many stakeholders and requiring consideration of many aspects of the organization, including clinical, structural, administrative, and cultural factors. The many challenges that will be faced in the effort to implement RME are the basis for the need to assess user readiness and acceptance. One model that can be used to assess RME implementation readiness is the Technology Readiness and Acceptance Model (TRAM). TRAM tries to explain how people adopt new technology. This study aims to analyze user readiness and acceptance in facing the demands of implementing RME at the NTB Provincial Hospital based on the Technology Readiness and Acceptance Model (TRAM). This study is a quantitative analytical study. The population in this study were all NTB Provincial Hospital officers involved in filling out medical records with a sample size of 87 people. The study's findings, analyzed through Partial Least Squares (PLS), reveal that Innovativeness (INN) exerts the strongest influence on Perceived Ease of Use (PEOU) with a ?-value of 0.434. Additionally, PEOU shows the most significant impact on Intention to Use (USI) with a ?-value of 1.106